Protokół wojny jako element protokolaryzacji bezpieczeństwa - Artur Gruszczak (Politeja)
WAR PROTOCOL AS AN ELEMENT OF SECURITY PROTOCOLARIZATION: THE CASE OF THE RUSSIAN MILITARY AGGRESSION AGAINST UKRAINE